Tastafi Organisasi Keagamaan Ulama Dayah di Aceh - Zulfikar Zulfikar; Muhibuddin Muhibuddin (CV. Ulil Albab Corp, 2022)
Tasawuf, Tawhid and Fiqh (TASTAFI) is a religious organization proclaimed by one of the dayah clerics, namely Teungku Hasanoel Bashry or now more popularly known as Abu MUDI, where this tastafi religious organization has been organized at the central level and the administrators have also been appointed. on the night of April 17 2018 in the courtyard of the Banda Aceh Grand Mosque which was also attended by the Governor of Aceh, the Mayor of Banda Aceh, Members of the Aceh Representative Council, Members of the Banda Aceh City Representative Council and other Acehnese community leaders. The Tastafi religious organization comes with a different feel from other organizations, where all the organization's administrators are dayah leaders in Aceh and this organization has received an extraordinary response and appreciation from the Acehnese people. This tastafi religious organization has been formed at the central, district/city level, there are even several sub-districts that have formed this organization. The purpose of establishing the Tastafi religious organization is to provide religious studies and studies, da'wah to the community by conveying and grounding the teachings of Tasawuf, Tawhid and Fiqh (TASTAFI) based on Ahlusunnah wal Jamaah, and protecting places of religious education such as dayah, recitation halls, taklim assemblies, religious councils. remembrance and society from heretical teachings, liberalism, secularism and radicalism, as well as realizing a civil society life order.